Students’ perception of industrial internship programme - Renganathan, Sumathi (Emerald, 2012)
Purpose – An important aspect of an academic curriculum in higher learning institutions for technical disciplines is the industrial internship programme for students. The purpose of this paper is to investigate students’ perception of the effectiveness of an industrial internship programme offered by a private technological university in Malaysia.